A Simplified Herbal Formula Improves Cardiac Function and Reduces Inflammation in Mice Through the TLR-Mediated NF-κB Signaling Pathway - Dong, Xiaoming; Han, Xiaowei; Zhang, Xiaojiao; Li, Sijing; Li, Ziru; Kang, Jinhua; Jiang, Jialin; Ni, Shihao; Lu, Lu; He, Zhiling; Huang, Haoming; Xian, Shaoxiang; et al. (Frontiers in Pharmacology, 2022)
Nuanxinkang tablet (NXK), a Chinese herbal formula, can improve heart function and quality of life in patients with chronic heart failure (CHF). However, the mechanisms of action of NXK are not fully understood. In this study, we investigated the effects of NXK on inflammation in the CHF mouse model. This model was established by transverse aortic constriction (TAC) and treated with NXK for eight weeks. Then, the cardiac function and myocardial fibrosis were evaluated. The monocytes/macrophages were evaluated by immunofluorescence. The mRNA levels of IL-1, IL-6, TNF-, ICAM-1, and VCAM-1 were measured by quantitative real-time polymerase chain reaction (qRT-PCR), while TLR4, MyD88, NF-B p65, P-IκBα, TLR2, TLR7 and TLR9 protein levels were evaluated by Western blot. The results showed that NXK improved the left ventricular ejection fraction (LVEF) and left ventricular end-systolic dimension, reversed myocardial fibrosis, and inhibited pro-inflammatory (CD11b+Ly6C+) monocytes/macrophages in the TAC mouse model. NXK also reduced the mRNA and protein levels of the above markers. Taken together, NXK improved heart function and reduced inflammation through the TLR-mediated NF-κB signaling pathway, suggesting that it might be used as an innovative treatment strategy for CHF.